The Mongol storm : making and breaking empires in the medieval Near East - Morton, Nicholas, 1980- (Basic Books, Hachette Book Group, 2022)
"The Mongol Storm is an epic account of violent conflict unfolding against the vibrant backdrop of the Seljuk Turks' magnificent garden palaces, mighty Crusader fortresses, Egyptian pyramids, Damascus' sprawling markets, and the vast Mongol wagon cities. Vividly written and vast in scope, it completely revises our understanding of the Mongols and the world of the Middle Ages"--